Departures from the protocol during conduct of a clinical trial: a pattern from the data record consistent with a learning curve. Issue 5 (10th August 2010) - Taekman, J M; Stafford-Smith, M; Velazquez, E J; Wright, M C; Phillips-Bute, B G; Pfeffer, M A; Sellers, M A; Pieper, K S; Newman, M F; Van de Werf, F; Diaz, R; Leimberger, J; et al.
Abstract : Objective: Recognition of learning curves in medical skill acquisition has enhanced patient safety through improved training techniques. Clinical trials research has not been similarly scrutinised. The VALsartan In Acute myocardial iNfarcTion, a large multinational, pragmatic, randomised, double-blind, multicentre trial, was retrospectively evaluated for evidence of research conduct consistent with a performance "learning curve". Design: Records provided protocol departure (deviations/violations) and documentation query data. For each site, analysis included patient order (eg, first, second), recruitment rate and first enrolment relative to study start date. Setting: Computerised data from a trial coordinated by an academic research organisation collaborating with 10 academic and 2 commercial research organisations and an industry sponsor. Interventions: 931 sites enrolled 14 703 patients. Departures were restricted to the first year. Exclusions included patient's death or loss to follow-up within 12 months and subjects enrolled 80th or higher at a site. Departures were assessed for variance with higher patient rank, more frequent recruitment and later start date. Methods and results: 12 367 patients at 931 sites were analysed. Departures were more common for patients enrolled earlier at a site (p<0.0001). For example, compared with the 30th patient, the first had 47% more departures. Departures were also more common with slower enrolment and site start closer to the trial start date (p<0.0001). Similar patterns existed for queries. Conclusions: Research performance improved during the VALsartan In Acute myocardial iNfarcTion consistent with a "learning curve". Although effects were not related to a change in outcome (mortality), learning curves in clinical research may have important safety, ethical, research quality and economic implications for trial conduct.